VizieR Online Data Catalog: CzeV1731 times of eclipses and radial velocities (Zasche+, 2020) - Zasche, P.; Henzl, Z.; Lehmann, H.; Pepper, J.; Powell, B. P.; Kostov, V. B.; Barclay, T.; Wolf, M.; Kucakova, H.; Uhlar, R.; Masek, M.; Palafouta, S.; et al. (2020)
The discovery and analysis of the system CzeV1731 represents a rare configuration of a 2+2 quadruple star system containing two eclipsing binaries, the third system of its kind known to date. The system under investigation in this work is TYC 3929-724-1 (= 2MASS J19245582+5704084 = TIC 284482112), located at RA=19:24:55.82, DE=+57:04:08.39, with Vmax=10.5mag. We present times of eclipses and radial velocities of both pairs. (2 data files).
Keywords: binaries: eclipsing; Radial velocities